Design of MPPT Algorithms using Simulink Support Package for Arduino Hardware - Channareth Srun; Phok Chrin; Sokchea Am; Bunthern Kim (International Journal of Engineering, Science and Information Technology, 2022)
In this paper, the performance of the DC-DC converter is assisted by MPPT control in a comparison between Perturb & Observe (P&O) and Incremental Conductance (IC) using the Simulink Support Package for Arduino Hardware. In photovoltaic systems, the maximum power point tracking needs to be powered by PV panels. A microcontroller controls the power converter. Before it is designed, the system is first modeled and simulated using MATLAB/Simulink. The control software implements a pulse-width modulation signal generator embedded in the Arduino microcontroller. The many stages of design for these controllers are discussed, along with simulation and experimentation. The system is tested, and the irradiance varies from 500 w/m2 to 1000 w/m2. The results of this simulation and experiment show that the plan with MPPT and a P&O controller has a higher efficiency of PV power production.